2015
DOI: 10.1155/2015/374013
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Eight Commercial Mushrooms by Electronic Nose and Gas Chromatography-Mass Spectrometry

Abstract: Volatile profiles of eight mushrooms were characterized by gas chromatography-mass spectrometry and electronic nose analysis. Volatile compounds including 11 alcohols, 11 ketones, 15 aldehydes, 3 sulfur compounds and alkenes, 8 terpenes, 7 acid and esters, 5 heterocyclic compounds, 20 aromatic compounds, and 4 other compounds were identified. The overall aroma properties of the mushrooms were analyzed by the electronic nose. Results indicated that the e-nose sensors have the ability to accurately respond to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 49 publications
2
31
0
4
Order By: Relevance
“…() classified several mushroom species ( Pleurotus abalonus , Agrocybe aegirit , Hericium erinaceus , Grifola frondosa , Coprinus comatus , Boletus edulis , Lentinula edodes , and P. eryngii ) based on the volatile component analysis by GC and electronic nose in combination with PCA. The authors did not provide information on how many different samples were analyzed per mushroom species (Zhou et al., ). The chemometric analysis for the discrimination of the popular six mushroom species (white beech, brown beech, button, oyster, king oyster, and enoki) has not been previously reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…() classified several mushroom species ( Pleurotus abalonus , Agrocybe aegirit , Hericium erinaceus , Grifola frondosa , Coprinus comatus , Boletus edulis , Lentinula edodes , and P. eryngii ) based on the volatile component analysis by GC and electronic nose in combination with PCA. The authors did not provide information on how many different samples were analyzed per mushroom species (Zhou et al., ). The chemometric analysis for the discrimination of the popular six mushroom species (white beech, brown beech, button, oyster, king oyster, and enoki) has not been previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…Chemometric analysis on the data set of volatile compounds has been used for the differentiation of mushroom species (Gioacchini et al., ; Malheiro et al., ; Zhou et al., ). Zhou et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it was reported that this phenolic compound is present in wild plants and mushrooms. [20][21][22] Of note, BP has been widely used as a raw material for phosphite antioxidants and as an intermediate for the preparation of ultraviolet stabilizers as well. 23) According to previous reports, BP is an antioxidant with remarkable cytotoxic activity against cancer cells, 24,25) and it has been shown to decrease the degree of low-density lipoprotein (LDL)-oxidation.…”
Section: Discussionmentioning
confidence: 99%